dynamics of boric acid Sorption by boron-selective SB-type anionite - Igor N. Lipunov; Inna G. Pervova; Alexander F. Nikiforov; Irina A. Klepalova (Водное хозяйство России: проблемы, технологии, управление)
Investigation and choice of an effective sorbent are significant for protection of water bodies against boron The boron high concentration in natural waters produces toxic impact on aquatic biota due to its high biological activity. This paper studied the dynamics of boric acid sorption from aqueous solutions by polycondensation anionite SB-1 synthesized on the base of monoethanolamine and epichlorohydrin. The anion exchanger contained aminooxyethyl and alcohol functional groups in its structure.